RANCANG BANGUN SISTEM PENGUKURAN SUHU JARAK JAUH UNTUK SURVEY POTENSI ENERGI TERBARUKAN DI LINGKUNGAN KAMPUS UNPAD JATINANGOR - Jajat Yuda Mindara; Sahrul Hidayat; Sri Suryaningsih; Norman Syakir; Wahyu Alamsyah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Universitas Padjadjaran as one of the academic institrusi has a vision to participate development potential of renewable energy. In the development of renewable energies in particular solar energy, data about the potential of the sector in the region is very compulsory. One of the potential energy that its data has not owned a solar thermal energy.One way of measuring system of temperature remote environment is to use the sensor in the terminal stored a few hundred meters from the computer of the recipient. As the process of sending and receiving data can be done by using a Modem FM.  In this case the processing and data conversion transformation is the environmental temperature (T), follow by transformed of T to Voltage, then converted to frequency (V/F) and finally it is modulated. Existence of environmental temperature visualization on the computer screen as results of demodulasi, conversion of frequency to Voltage (F/V) and the conversion of Analog to Digital. In this study addressed the analysis of transformation and environmental temperature conversion to digital data with the design using a conditioned LM25 Tranducer to the Voltage (0 to 5) Volts comparable to (0 to 50) oC. Converter (V/F) and (F/V) vice versa is (0 to 5) Volts comparable to (0 to5000) Hz. And the conversion of analog to digital (0 to 65535) is proportional to the temperature. Based on its transformasion and the conversion state information designed normal temperature at between 24-27oC, state of heat above 27oC is hot and under 24 is coolKeywords: Temperature sensors, Converter (V/F), (F/V) FM, Modem, ADC.